CHARACTERISTIC FEATURES OF JUNIOR BACHELOR TRAINING IN SPECIALTY "NURSING" AT THE DEPARTMENT OF MEDICAL AND PHARMACEUTICAL CHEMISTRY OF BSMU - Stehnitska, Lyubov; Kropelnytska, Yulia; Velyka, Alla (SWorldJournal, 2022)
The authors consider the primary teaching and curriculum development approaches in the discipline of “Medical Chemistry” for students of specialty “Nursing” based on a credit-module system at the Professional College of Bukovinian State Medical Universit